2013
DOI: 10.4067/s0718-07642013000500011
|View full text |Cite
|
Sign up to set email alerts
|

Optimización del Proceso de Extracción de Antocianinas y Evaluación de la Capacidad Antioxidante de Berenjena (Solana melonera L.)

Abstract: El objetivo de esta investigación fue optimizar el proceso de extracción de antocianinas obtenidas de berenjena (Solanum melongena L.) y evaluar su capacidad antioxidante. A extractos de piel y pulpa se le realizaron análisis fisicoquímicos, contenido en fenoles y antocianos. Para la optimización del proceso de extracción de las antocianinas se empleó la metodología de superficie de respuesta con tres factores: concentración de solvente etanol acidificado 1% ácido ortofosfórico (50 a 90% v/v), temperatura extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
1
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 24 publications
5
11
1
10
Order By: Relevance
“…4 An analysis performed with the eggplant pulp showed a concentration of 62.5 mg gallic acid equivalent/100 g in the fresh pulp. 23 This value is lower than that found in the present study with EF prepared from the whole fruit, which was 1,540 mg gallic acid equivalent/100 g in the flour. This is an expected result, since eggplant skin is rich in polyphenols and 100 g EF represent 1,000 g of the fruit.…”
Section: Discussioncontrasting
confidence: 55%
“…4 An analysis performed with the eggplant pulp showed a concentration of 62.5 mg gallic acid equivalent/100 g in the fresh pulp. 23 This value is lower than that found in the present study with EF prepared from the whole fruit, which was 1,540 mg gallic acid equivalent/100 g in the flour. This is an expected result, since eggplant skin is rich in polyphenols and 100 g EF represent 1,000 g of the fruit.…”
Section: Discussioncontrasting
confidence: 55%
“…San José et al 2013found pH of 5.44. Heras et al (2013), analyzing fruits of the eggplant cultivars 'Morada' and 'Lila' , found pH values of 5.59 and 4.47 and acidity of 0.14 and 0.2% of citric acid, respectively. These characteristics, which are associated with fruit quality, directly influence the taste.…”
Section: Resultsmentioning
confidence: 99%
“…According to the many authors, the extraction time can either be as short as a few minutes or very long, up to 24 h. In this study, the range of extraction time was established based on practical and economical aspects (15–240 min). Heras et al [30] mentioned that in anthocyanin extraction (main antioxidant compounds in berries) after an over prolonged time it could not be significant to pigment extraction. The Fick’s diffusion law predicted that after certain time there will be a final equilibrium between the matrix solutes and the extraction solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Along all extraction time range studied, no significant influence on the ORAC value for the three solvents is observed. Therefore, it could be backed up that extraction treatment at high temperatures and prolonged time causes a decrease on the antioxidant capacity according to Heras et al [30], due to the long extraction process period that could be give rise to phenolic compounds oxidation because of the light, the exposition to oxygen and degradation. It seems that extraction time in berries of smaller diameter (4–6 mm approx.)…”
Section: Resultsmentioning
confidence: 99%